Efficacy of Centella Asiatica in Reducing Oxidative Stress in Hydrogen Peroxideinduced Sprague Dawley Rats - Hussin, Mahanom (2005)
Centella asiatica is one of the local medicinal plants that have been claimed to have various medicinal effects.The study was designed to investigate the effect of Centella asiatica extract and powder on blood lipid profile,blood lipid peroxidation and antioxidant enzymes activity in oxidative stress induced male Sprague Dawley rats. In the first phase of the study, the experimental rats were fed with 0.3% (w/w)Centella asiatica extract, 1.5% (w/w) Centella asiatica powder, 5.0% (w/w) Centella asiatica powder and 0.3% (w/w) α-tocopherol for 6 weeks.Oxidative stress in these rats was induced by giving them 0.03% (v/v) hydrogen peroxide (H2O2) in drinking water. Normal rats were provided with commercial Gold Coin diet. Malonaldehyde (MDA) level and activities of catalase (CAT),superoxide dismutase (SOD) and glutathione peroxidase (GPx) before and during treatments were monitored.Histopathological examination of selected organs was done at the end of the study. The results showed that MDA level was significantly (p<0.05) higher in the normal rats compared to others. Dietary supplementation of Centella asiatica (extract and powder) and α-tocopherol significantly (p<0.05) reduced lipid peroxidation in the experimental rats. However, there was no significant differences in the activities of antioxidant enzymes and histopathology observations of the organs of the rats.H2O2 (0.05%, 0.10% and 0.15%) were given to rats via drinking water for 6 weeks in determining effective H2O2 level in inducing oxidative stress in the experimental rats.At the end of the study, the experimental rats were sacrificed and organs namely heart, liver and kidney were weighed and fat content of the organs was determined. Results showed that rats treated with 0.10% (v/v) and 0.15%(v/v) H2O2 had significantly (p<0.05) increased MDA level compared to that of normal and 0.05% (v/v) H2O2 treated rats. The finding suggested that supplementation of 0.10% (v/v) and 0.15% (v/v) H2O2 are sufficient in inducing oxidative stress in the experimental rats.Second phase of the study was conducted using increase level of H2O2 and prolong duration of the treatments. Experimental rats were fed with 0.3% (w/w) Centella asiatica extract, 5.0% (w/w)Centella asiatica powder and 0.3% (w/w) α-tocopherol for 25 weeks. Oxidative stress was induced by giving the rats 0.1% (v/v) H2O2 in drinking water. Normal rats were provided with commercial Gold Coin diet. Blood lipid profile [cholesterol, high density lipoprotein (HDL),low density lipoprotein (LDL) and triacylglycerol (TG)], MDA, CAT and SOD activities in experimental rats were monitored throughout the treatments. Histopathological examination of the heart, liver and kidney of the rats was done after the treatments ended. Results of the study indicated that Centella asiatica extract and powder significantly (p<0.05) increased serum HDL and cholesterol level compared to normal rats.Centella asiatica extract and powder also significantly lowered serum TG and LDL concentrations compared to normal rats at the end of the study. Results also showed lowered MDA levels in experimental rats consuming Centella asiatica extract, powder and α-tocopherol. The decrease in the activity of SOD and increase in CAT activity in Centella asiatica and α-tocopherol supplemented rats as compared to normal rats appeared to be the response towards decreased in free radical formation and prevention of H2O2 accumulation respectively.Histopathological examination of the heart, liver and kidney revealed no obvious changes in Centella asiatica-fed rats. The results suggested that long-term consumption of Centella asiatica extract and powder is not toxic to heart, liver or kidney. Results also revealed that Centella asiatica extract and powder may ameliorate H2O2-induced oxidative stress by increasing HDL concentration, decreasing the level of TG, LDL, lipid peroxidation and altering antioxidant defense system in experimental rats.These effects may be attributed to the antioxidant components and polyphenol substances present in Centella asiatica